(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Panasa (Artocarpus heterophyllus Lam), the well known jackfruit tree is widely distributed all over the world. It is a treasure trove of various ethnomedical uses which are yet to be proven scientifically. Its fruit is very delicious and its leaves, root, latex, seed and wood are reported to have many medicinal properties. Though the plant is renowned for its nutritive values, the useful parts of the plant with rich medicinal values are less utilized for medicinal purposes. The plant is well described in Ayurvedic classics where prime importance has been given to its fruit whereas least references are available concerned to its other useful parts especially the leaf. This forms the literature gap concerned with this drug that hinders its further clinical researches. A compiled review of the classical literature of Panasa is not yet available as a ready reference. Hence it is a herculean task for the researcher to compile the literature which is scattered in various classical books of different era. In this work focus has been made to compile the literature of the plant Panasa (Artocarpus heterophyllus Lam) from the Ayurvedic classics. As this work provides the literature of this plant under a single roof it will be helpful for the scholars in future research works.